The effect of foliar fertilizer dosage variations to the growth and productivity of some fruit vegetables exposed to manipulated grasshopper sound - Ratnawati Ratnawati; Agus Purwanto; Budiwati Budiwati; Suratsih Suratsih; Rahma Ayu Maharani; Decy Lukitasari (Jurnal Sains Dasar, 2014)
The study aims to investigate the optimal dosage of foliar fertilizer to the growth and productivity of  some fruit vegetables exposed to manipulated grasshopper sound  on the frequency of 4500 Hz. “Intan” variety tomato,“Kresna” variety chili and “parade tavi” variety snake bean was treated in 6 dosages of foliar fertilizer, This research is an experimental research using randomized blok design conducted from December,2012 to October, 2013 at Rowobayem, Kabupaten Purworejo, at Ngalas, Kabupaten Klaten, and at Kricaan, Mesir,  Salam Kabupaten Magelang. Parameters measured were the area of stomatal opening, leaf area, plant fresh weight, plant dry weight and the yield. Research results show that there is  a significant effect of dosage variation of foliar fertilizer on tomato plants  on the plant fresh weight, plant dry weight, and tomato weight; on chili plants  on leaf fresh and dry weight, dry weight of leaf and chili weight. Meanwhile,  the optimal dosage of foliar fertilizer for tomato plants is 1.75 cc/l, for chili plants is 1.25 g/l and that for snake bean plants is 1.25 g/l. Key words: sound wave, chili, tomato, snake bean, growth